The Effectiveness of Entrepreneurial Education Programs in Kenya - Chege Salem Kabue (GoAcademica Research & Publishing, 2022)
There has been a shift toward placing an excessive amount of focus on financial, legal, and regulatory factors, as well as environmental variables, in entrepreneurship courses. The research team in this study set out to answer the question,